PHYSICAL ACTIVITY OF PREGNANT WOMEN AND ITS BARRIERS IN KULON PROGO, YOGYAKARTA - Maulana Ikhsan; Indriani Indriani; Ummy Aisyah Nurhayati (Keperawatan Anestesiologi Program Sarjana Terapan, 2024)
Background: Physical activity (PA) provides many benefits for maintaining maternal and fetal health during normal pregnancy. PA recommendations for pregnant women are light intensity for 150 minutes per week. Several barriers such as busy work, lack of motivation and knowledge are the reasons for physical activity constraints in pregnant women. Objective: To determine physical activity in pregnant women and its obstacles in Kulon Progo, Yogyakarta. Methods: Cross-sectional study on pregnant women in the first, second, and third trimester in one clinic in Kulonprogo, Yogyakarta from June-August 2024. The population was registered pregnant women with a sample size of 110 pregnant women with inclusion and inclusion criteria. The research instrument used the Pregnancy Physical Activity Questionnaire (PPAQ) and the Exercise Benefits/Barriers Scale (EBBS) questionnaire. Data analysis using Chi-square with SPSS version 27: Of the 110 respondents, most of the physical activity was in the light category, namely 54 respondents (49.1%) and in the activity type category, namely inactive 65 respondents (59.1%). There is a relationship between occupation (P = 0.053), parity (P = 0.003), BMI (P = 0.027) and constraints (P = 0.000) and there is no relationship between age and gestational age (P => 0.005). Conclusion: Most pregnant women had mild physical activity and many were inactive. There was a significant relationship between occupation, parity, BMI, and constraints to physical activity, while age and gestational age were not significant. The government needs to increase education about the importance of physical activity during pregnancy, and collaboration between health workers and academics should be improved to overcome the constraints faced, including providing accessible exercise programs.